An Evolutionary Look at Football Soccer Celebration - Monge, Julián (Universidad de Costa Rica, 2019)
Football can be considered a symbolic struggle in which humans use behavioral mechanisms that evolved in hominid clans. Women, children and the elder are notably absent in most football violence. My observation of 50 groups celebrating 2014 World Cup results on the Costa Rican streets found that both sexes and all age groups participated equally, probably because group participation on the streets was safe, with violence concentrated in stadiums and inside homes.